Profiling Nurse Practitioner practice patterns at a major urban acute health service. Issue 3 (June 2018) - Lowe, Grainne; Jennings, Natasha; Tregaskis, Peter; Kenneally, Anne; Bucknall, Tracey
Abstract: Background: Research detailing the practice patterns and services provided by nurse practitioners within a large health care facility is currently lacking in the literature. This study fills a gap in the literature by reporting on the practices of nurse practitioners in a variety of clinical specialty areas within the one health care setting. Aim: To identify the practices of nurse practitioners in different contexts across one health service. BackgroundAn expanding cohort of nurse practitioners within an Australian health service increasingly delivers services to more complex patients. Understanding this phenomenon assists future workforce planning. Methods: An exploratory survey of nurse practitioner practice patterns in a metropolitan health service was conducted. Nurse practitioners electronically entered data from patient encounters for two weeks. Descriptive analysis of the quantitative data was conducted. Results: Nine nurse practitioner specialties were identified and 341 encounters were analysed. All specialty groups included counselling and education in patient management. The use of nurse practitioner extensions to practice was dependent on the specialty area including prescribing medicines. Conclusions: Nurse practitioner scope of practice differs across specialties and is determined by patient cohorts and associated diagnoses. The results highlighted the diversity and depth of services provided by nurse practitioners. Understanding the scope of practice assist with future nurse practitioner role development andimplementation.